THE ROLE OF LITERARY WORK AS A PRODUCT OF CREATIVE INDUSTRY TOWARDS ASEAN ECONOMIC COMMUNITY - Mutiarani Mutiarani (Proceedings Education and Language International Conference, 2017)
The presence of the ASEAN Economic Community in 2015 is the free market that provides the opportunity to continue to innovate and enhance creativity so that they can compete in the global competition. These opportunities provide an opportunity for the development of creative industries based languages namely literature. The literary work is the result of human creativity will be full of ideas, feelings and messages. The literary work has similarities with the creative industries which are both based on the work of human creativity and full of cultural nuances. However, both have differences on the process of creation, literary works were created for the sake of form and literary interests while the creative industries are created based on the needs of the market both as a representation of culture as well as entertainment media. This study aims to identify the role of literature as one of the creative industry products to ASEAN Economic Community. It is a qualitative study that relates some theories in the role of a literary work as a product of the creative industries to the ASEAN Economic Community. The data were collected by library research. The findings showed that; 1). The literary work has an important role as a cultural product that is capable of being a cultural ambassador in ASEAN, 2). Literary works such as novels and movies is a language-based creative industry product as potential commodities that were able to take good advantage of foreign exchange for the country as well as royalties for its creators, 3). Literary product such as novels and movies as entertainment products are able of providing promising business opportunities in ASEAN.Keywords: Asean economic community, creative industry, literary work